Development of a humanized mouse model to analyze antibodies specific for human leukocyte antigen (HLA). - Senichiro Yanagawa; Hiroyuki Tahara; Takayuki Shirouzu; Shintaro Kawai; Yuka Tanaka; Kentaro Ide; Shuji Akimoto; Hideki Ohdan (PLoS ONE, 2021)
In organ transplantation, human leukocyte antigen (HLA)-mismatch grafts not only induce the activation of cellular mediated immune response but also the development of chronic antibody-mediated rejection due to the donor-specific anti-HLA antibody (DSA) produced by B cells and plasma cells interacting with the graft endothelium. Significant improvement in long-term survival after transplantation can be expected if antibody-mediated rejection due to the DSA can be overcome. However, the mechanism of producing or controlling the DSA remains to be elucidated. In recent decades, "humanized" mouse models have been widely used for the basic research of human immune systems, but a humanized mouse model to analyze the mechanism of DSA production has not been established yet. Thus, we aimed to create a humanized mouse using a severe immunodeficiency mouse (NSG mouse) administered with human peripheral blood mononuclear cells (PBMCs). Initially, we detected a very low level of human total-IgG and no anti-HLA antibodies (Abs) in these mice. In our next attempt, we mixed PBMCs of various HLA antigenic combinations with or without regulatory T cells and preconditioned them by culturing on feeder cells stably transfected with human CD40 ligand (h-CD40L) alone or with h-CD40L and human B cell activating factor (h-BAFF). They were subsequently co-cultured with the corresponding irradiated stimulator PBMCs, and all cells were administered into naïve NSG mice. Although all three humanized models had sufficient human total-IgG and anti-HLA antibody production, allospecific anti-HLA Ab production was prominently suppressed whereas non-specific anti-HLA Abs were sufficiently detected. Therefore, this novel humanized mouse model might be useful for analyzing the mechanism of anti-allogeneic human B cell tolerance induction.